Sur une espèce nouvelle dans la faune teuthologique de Tunisie: <Ocythoe tuberculata> Rafinesque, 1814 (Cephalopoda, Octopoda) - EZZEDDINE-NAJAI, Soufia; EL ABED, Amor (INSTM Bulletin : Marine and Freshwater Sciences, 2001)
A species of Cephalopod has been identified for the first time in the north of Tunisian waters; it is about Ocythoe tuberculata Rafinesque, 1814, an uncommon pelagic octopus in the Mediterranean. The animal of 31.5 cm length mantle is among the biggest female reported from the species.